Determination of 35 Free Amino Acids in Tea Using Ultra-Performance Liquid Chromatography Coupled With Quadrupole Time-of-Flight Mass Spectrometry - Li, Jian; Ma, Junmei; Li, Qiang; Fan, Sufang; Fan, Lixin; Ma, Hongyu; Zhang, Yan; Zheng, Lei (Frontiers in Nutrition, 2021)
The purpose of this research was to develop a simple, sensitive, and accurate method for simultaneous determination of 35 free amino acids using ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Tea samples were extracted with boiling water bath, and then separated by XBridge BEH Amide column by gradient elution. The exact mass and MS/MS spectra of the target compound was detected under the TOF–MS and Information dependent acquisition (IDA)–MS/MS mode. The results demonstrated good linearity (R2 > 0.9980) in the range of 0.5–1,000 ng/mL. The limits of detection (LODs) were 0.13–25.00 mg/kg and the limits of quantitation (LOQs) were 0.25–50.00 mg/kg. The recovery rate ranged from 70.1 to 105.1% with relative standard deviations (RSDs) <11% (n = 6). This research provides a targeted strategy for developing an analysis method for amino acids in tea.